(untitled) (Research, Society and Development, 2023)
Introduction: Electronic cigarettes have gained prominence and popularity since 2003. Use is more prevalent in the 19-24 age group. Lung diseases, cardiovascular, immunological, dermatological and oral disorders, resulting from the toxic effects provided by the various compounds of the product, are a possible problem for the future of public health. Objective: To identify the toxic effects of electronic cigarette use on the physiological mechanisms of the human body. Materials and Methods: This is an integrative literature review about the new evidence on the toxic effects of electronic cigarettes and the pathophysiology involved. The PICO strategy was used to prepare the guiding question. In addition, these descriptors were crossed; “electronic cigarette”; “toxicity”; “pathophysiology”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (BVS) databases. Results and Discussion: The vast majority of articles showed a harmful relationship between the use of electronic cigarettes and various systems, such as exacerbation of asthma and chronic obstructive pulmonary disease, increased risk of thrombosis and atherosclerosis, alteration in the functioning of macrophages and platelets, the reduction of nitric oxide and other mechanisms. Conclusion: Several pathophysiological mechanisms have been elucidated in several studies, but it is necessary that more studies, especially longitudinal and with the identification of the pattern of use and the components of e-cigarettes, be developed to consolidate the evidence already proposed, especially in the long term.